The Study of Ravandiyeh Thought and its Impact on the Abbasid Caliphate - BAHMANI, MORTEZA ALI; GOLJAN, MAHDI (The journal of contemporary issues in business and government, 2021)
After the death of Prophet Muhammad (PBUH), the most important difference that gave rise to subsequent factions was the challenge of determining successor. A group that believed in a will and a group that tried to give the community their choice. A large group of people who came to the political area because of this challenge was a Shiite, which included several streams. Abbasid currents included many currents, most notably Ravandiyya, which were considered extremes and recognized the Imamate of the Abbasids and had a far-reaching view of the Imams. After the killing of Abu Muslem, they rose in the Mansour era and were suppressed by the caliphate, but their views on the issue of Imamate were accepted in the Mahdi period. The purpose of the present study is to investigate Ravandiyeh's view of Imamate and its impact on the future of the Abbasid caliphate.